1999
DOI: 10.1103/physrevlett.82.2171
|View full text |Cite
|
Sign up to set email alerts
|

Charge Conveyance and Nonlinear Acoustoelectric Phenomena for Intense Surface Acoustic Waves on a Semiconductor Quantum Well

Abstract: The combination of semiconductor quantum well structures and strongly piezoelectric crystals leads to a system in which surface acoustic waves with very large amplitudes can interact with charge carriers in the well. The surface acoustic wave induces a dynamic lateral superlattice potential in the plane of the quantum well which is strong enough to spatially break up a two-dimensional electron system into moving wires of trapped charge. This transition is manifested in an increase of the electron transport vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 20 publications
4
71
0
Order By: Relevance
“…6͑c͒ indicates that not all photogenerated carriers are transported within a single cycle of the SAW. A similar spreading of the detection time was observed recently by Rotter et al 17 during the unipolar transport of electrons by SAW's in two-dimensional electron gases for low SAW amplitudes. In the case of ambipolar transport investigated here, the presence of several pulses is attributed to the partial screening of the piezoelectric field by photogenerated carriers.…”
Section: Carrier Dynamicssupporting
confidence: 85%
“…6͑c͒ indicates that not all photogenerated carriers are transported within a single cycle of the SAW. A similar spreading of the detection time was observed recently by Rotter et al 17 during the unipolar transport of electrons by SAW's in two-dimensional electron gases for low SAW amplitudes. In the case of ambipolar transport investigated here, the presence of several pulses is attributed to the partial screening of the piezoelectric field by photogenerated carriers.…”
Section: Carrier Dynamicssupporting
confidence: 85%
“…If one takes the liberal view of charge carriers in semiconductors as a fluid, or, more appropriately, as a gas (Hohenberg et al, 1964), the manipulation and transport of these charge carriers can represent an extension of what is presented in this review. Simple SAW can be used to transport charge carriers in semiconductor quantum well structures fabricated in thin-film GaAs=InGaAs atop LN (Rotter et al, 1999) to even form moving quantum dots as reported by Fletcher et al (2003), naturally leading to the use of such quantum dots in quantum computing by Furuta et al (2004) and even SAW-induced luminescence (Gell et al, 2006) in the quest to obtain a single-photon source. Aside from quantum applications, the ability to transport charge within semiconductors offers interesting applications in UV detectors using epitaxial ZnO thin films (Emanetoglu et al, 2004) and ZnO nanoparticles (Chivukula et al, 2010), and even solar cells (Yakovenko et al, 2009).…”
Section: A Improvement Of Analysis Techniquesmentioning
confidence: 99%
“…For axial NW based QDs key experiments including ultra-bright single photon emission [9], quasi-static charge state control [10] and optical initialization of spin states [11] clearly underpinned the large potential of these systems. Radio frequency surface acoustic waves (SAWs) represent a particularly attractive and powerful tool to probe and dynamically control charge excitations in semiconductor heterostructure including Quantum Hall systems [12,13,14], charge transport in oneand two-dimensional electron channels [15,16], transport of charges [17,18,19], spins [20] or dipolar excitons [21] and precisely timed carrier injection into QDs for low-jitter single photon emission [22,23,24,25]. Recently, these concepts have been transferred to intrinsic nanowires (NWs) [26] and nanotubes [27] and NWs containing complex radial and axial heterostructures [28,29,30].…”
Section: Introductionmentioning
confidence: 99%